Cell-Free Biological Approach for Corneal Stromal Wound Healing - Jhanji, Vishal; Billig, Isabelle; Yam, Gary Hin-Fai (Frontiers in Pharmacology, 2021)
Corneal opacification is the fourth most common cause of blindness globally behind cataracts, glaucoma, and age-related macular degeneration. The standard treatment of serious corneal scarring is corneal transplantation. Though it is effective for restoring vision, the treatment outcome is not optimal, due to limitations such as long-term graft survival, lifelong use of immunosuppressants, and a loss of corneal strength. Regulation of corneal stromal wound healing, along with inhibition or downregulation of corneal scarring is a promising approach to prevent corneal opacification. Pharmacological approaches have been suggested, however, these are fraught with side effects. Tissue healing is an intricate process that involves cell death, proliferation, differentiation, and remodeling of the extracellular matrix. Current research on stromal wound healing is focused on corneal characteristics such as the immune response, angiogenesis, and cell signaling. Indeed, promising new technologies with the potential to modulate wound healing are under development. In this review, we provide an overview of cell-free strategies and some approaches under development that have the potential to control stromal fibrosis and scarring, especially in the context of early intervention.